Determination Analysis of Online Investment Intention in Post-Pandemic Era - Ricardo Julio Mamahit; S.L.H.V. Joyce Lapian; Emilia M. Gunawan (Universitas Sam Ratulangi, 2022)
Increased investment is an important factor in determining income level. Increasing investment can be done by increasing the intention to invest first. Investment intention is a feeling of wanting to pay attention to investment activities or wanting to invest. Therefore, to increase public investment intention, especially in post-pandemic era, it is necessary to know what factors influence this intention, and how they affect it. This study aims to analyze the influence of Financial Literacy, Perceived Risk and Subjective Norms on Online Investment Intention. This research was conducted using quantitative methods. Multiple Regression Analysis method is used to analyze the influence of the independent variables toward the dependent variable. Sample were taken from the millennial generation in Manado City with a total sample of 100 respondents. The results of this study indicate that Financial Literacy and Subjective Norm have a positive and significant influence on Online Investment Intention, while Perceived Risk has a negative and significant influence on Online Investment Intention. The results also indicate that Financial Literacy, Perceived Risk and Subjective Norms simultaneously influence Online Investment Intention positively and significantly.